Looking for the ideal medication for heart failure with reduced ejection fraction: a narrative review - Pascual-Figal, Domingo; Bayes-Genis, Antoni (Frontiers in Cardiovascular Medicine, 2024)
The main goals of the pharmacological treatment of Heart failure with reduced ejection fraction (HFrEF) are the reduction of mortality and the prevention of hospitalizations. However, other outcomes such as improvements in cardiac remodeling and clinical status, functional capacity and quality of life, should be taken into account. Also, given the significant inter-individual and intra-individual variability of HF, and the fact that patients usually present with comorbidities, an appropriate treatment for HFrEF should exert a clinical benefit in most patient profiles irrespective of their characteristics or the presence of comorbidities, while providing organ protection beyond the cardiovascular system. The aim of this narrative review is to determine which are the proven effects of the guideline-directed treatments for HFrEF on five key clinical outcomes: cardiovascular mortality and hospitalization due to HF, sudden death, reverse cardiac remodeling, renal protection and evidence in hospitalized patients. Publications that fulfilled the pre-established selection criteria were selected and reviewed. Renin-angiotensin system (RAS) inhibitors, namely angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin II receptor blockers (ARBs) or angiotensin receptor-neprilysin inhibitors (ARNI), beta-blockers (BB), mineralocorticoid receptor antagonists (MRA), sodium-glucose co-transporter 2 inhibitors (SGLT2i) show a benefit in terms of mortality and hospitalization rates. ARNI, BB, and MRA have demonstrated a significant positive effect on the incidence of sudden death. ARB, ARNI, BB and SGLT2i have been associated with clear benefits in reverse cardiac remodeling. Additionally, there is consistent evidence of renal protection from ARB, ARNI, and SGLT2i in renal protection and of benefits for hospitalized patients from ARNI and SGLT2i. In conclusion, the combination of drugs 4 that gather most beneficial effects in HFrEF, beyond cardiovascular mortality and hospitalization, would be ideally pursued.